2017
DOI: 10.5114/fmpcr.2017.69275
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of risk factors of recurring non-specific low back pain with particular emphasis on “new” predictive factors

Abstract: Background. non-specific low back pain (nSLBP) is one of the most frequent causes of medical consultations. the recurrence rate is high and estimated to be within the range from 25% to 70% in different populations. currently, the contribution of various predictive factors of nSLBP is being discussed. what seems to be interesting are studies on the impact of chronic diseases on the occurrence of nSLBP. Objectives. the purpose of this paper is to assess the frequency and analyse the risk factors of recurring nSL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 30 publications
0
5
0
1
Order By: Relevance
“…Numerous studies and analyses focused on the excessive strain of the spine and its consequences to health. It was demonstrated that even 2/3 of people below 40 years of age suffered from at least one episode of low back pain and over 60% of them experience a recurrence of pain within the same year [ 2 , 12 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Numerous studies and analyses focused on the excessive strain of the spine and its consequences to health. It was demonstrated that even 2/3 of people below 40 years of age suffered from at least one episode of low back pain and over 60% of them experience a recurrence of pain within the same year [ 2 , 12 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…An acute pain episode which had occurred ≥ 3 times in the last 12 months was considered “recurring” low back pain [ 1 , 12 ]. Chronic back pain is defined as pain that persists for 12 weeks or longer [ 1 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Este resultado es compatible con un estudio realizado en Finlandia, pues los resultados dieron positivos tras un análisis de triglicéridos y colesterol séricos en pacientes con lumbalgia crónica localizada o difusa (20) Años previos, hallazgo fue igualmente referido en un estudio prospectivo en Estados Unidos, en el que documentan asociación positiva entre la concentración de triglicéridos y el dolor lumbar referido por pacientes pensionados que han trabajado como oficinistas (21) . Citko et al encontraron que la hiperlipidemia aumentaba hasta 8 veces el riesgo de padecer lumbago en personal médico (22) .…”
Section: Pág 86unclassified